Multi-component block copolymerization composition as well as preparation method and application thereof

By controlling the vinyl aromatic content and molecular weight of the block copolymer composition, combined with a three-step and two-step polymerization process, a binder for polymer waterproof coil was prepared, which solved the initial adhesion and stickiness of hot melt adhesives in the hot melt adhesive The balance of force, peel strength and wetting properties has achieved improved high temperature stability and waterproofness and extended service life.

CN119192766AInactive Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310745361.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polymer waterproof coils are difficult to balance the initial adhesion, adhesion, peel strength and wetting properties of hot melt adhesives, resulting in repeated effects of cold, hot, dry and wet The problem of debonding and separation of the material layer from the cement base surface or polymer film layer.

Method used

By controlling the vinyl aromatic content, molecular weight and additive ratio in the multicomponent block copolymer composition, the block copolymer composition is prepared by a three-step and two-step polymerization process to form a composition with excellent comprehensive performance and used to Taper-enhancing resin and softener jointly prepare adhesives for polymer waterproof coils.

Benefits of technology

It achieves high peel strength of hot melt adhesive, good softener retention, excellent flexibility, and waterproof coils are not easy to displace at high temperatures and are not easy to crack at low temperatures, extending service life and improving waterproofness and aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004298803070000121
    Figure BDA0004298803070000121
  • Figure BDA0004298803070000122
    Figure BDA0004298803070000122
  • Figure BDA0004298803070000131
    Figure BDA0004298803070000131
Patent Text Reader

Abstract

The invention discloses a multi-component block copolymerization composition as well as a preparation method and application thereof. The block copolymerization composition is prepared from raw materials including a triblock copolymer A and a diblock copolymer B, the content of vinylarene in the triblock copolymer A is higher than the content of vinylarene in the diblock copolymer B, and the weight-average molecular weights of the triblock copolymer A and the diblock copolymer B are the same or close. The copolymer composition is prepared through a three-step polymerization method and a two-step polymerization method, and the polymer waterproof roll adhesive composition prepared from the copolymer composition has good flexibility, high initial adhesion and peel strength, good wettability and cohesiveness to a tire base layer and a polymer layer of a polymer waterproof roll, and good adhesion to the polymer layer and the base layer of the polymer waterproof roll. And the tackifying resin and the softening agent are further added and can generate a synergistic effect with the tackifying resin and the softening agent, so that the waterproofness of the macromolecular waterproof roll is greatly improved, and the service life of the macromolecular waterproof roll is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermoplastic block copolymer composition, in particular to a multi-component block copolymer composition and a preparation method and application thereof, belonging to the field of polymers. Background Art

[0002] As one of the important materials in the construction industry, waterproofing membrane is mainly used in building walls, roofs, foundation slabs, roads, tunnels, underground pipe galleries, landfills, etc. It is a flexible waterproof material that can prevent moisture and seepage. It is the first line of defense for waterproofing projects and plays a vital role in the entire project construction and use. At present, domestic waterproofing materials can be roughly divided into three categories: modified asphalt waterproofing membrane, polymer waterproofing membrane and waterproof coating.

[0003] These three categories have their own advantages and disadvantages. For example, modified asphalt waterproofing membrane is cheap, has good hydrophobicity, adhesion and ductility, can resist acid, alkali and salt corrosion, has good impact resistance and is easy to prepare. However, modified asphalt waterproofing membrane is easy to age and crack when heated, and is inconsistent with the thermal expansion and contraction of cement roofs or metal roofs, so it is easy to delaminate, has a short service life and poor chemical stability. Waterproof coatings have high requirements for the flatness, material and use environment of the base layer, are easily damaged, and are mostly used for kitchen and bathroom waterproofing. Polymer waterproofing membranes have achieved rapid growth due to their excellent air tightness, waterproofness, construction and environmental protection. Polymer waterproofing membranes have different properties due to different compositions, but polymer waterproofing membranes of different compositions still have certain limitations. For example, the puncture resistance and crack resistance are limited, the adhesion between the polymer mixture layer and the isolation membrane protective layer (also called the base layer) is insufficient, the compatibility with other materials needs to be improved, and the service life needs to be extended.

[0004] Polymer waterproofing membranes are generally composed of a polymer mixture layer and an isolation membrane protective layer (also called a base layer), and the two layers are bonded together by hot melt adhesive. Of course, there are other material layers added according to some special needs. If the bonding force between the polymer mixture layer and the isolation membrane protective layer is not enough, it will cause the problem of displacement between the polymer layer and the isolation membrane protective layer. In this regard, the Chinese patent (CN110408340 A) adopts the method of adding a modified asphalt adhesive layer between the polymer layer and the isolation membrane protective layer to increase the bonding force between the two; the Chinese patent (CN108130746 B) uses a fluidized bed to blow in microsphere particles carrying monomers, initiators, and cross-linking agents, so that they adhere to the upper and lower surfaces of polyester non-woven fabrics, and then cover them with modified plastics. The cross-linking reaction and hot melt bonding of the non-woven fabrics are simultaneously initiated by microwave radiation to obtain a polymer waterproofing membrane with firm bonding to the non-woven fabric; the Chinese patent (CN107603560 A) A double-reaction bonding polymer waterproofing membrane is mentioned, which includes a polymer film and a rubber layer, wherein the rubber layer can produce chemical reactions and bonding with the cement base surface, and can also produce chemical reactions and bonding with the polymer film layer, so as to achieve a double-reaction bonding effect, and completely solve the technical problems of debonding and separation of the rubber layer of the membrane from the cement base surface and the rubber layer of the membrane from the polymer film layer under the repeated effects of cold, heat, dryness and wetness in the actual application of the waterproofing membrane. However, the polymer film needs to be subjected to plasma surface treatment, and a coupling agent is added to the rubber layer to achieve a double-reaction bonding effect. This double reaction is not easy to stably control, and the overall preparation of the waterproofing membrane is complicated.

[0005] Most of the thermoplastic elastomer polymers used for hot melt adhesives are polymers with the following structures: linear polymers of polyvinyl aromatic hydrocarbons-polyconjugated diene-polyvinyl aromatic hydrocarbons, star-shaped polymers of (polyvinyl aromatic hydrocarbons-polyconjugated diene) nX, and mixtures of the two. The preparation process of polymers with linear structures is easy to control, the quality is stable, and the cohesion is strong, but the melt viscosity is high and the processing and use are inconvenient; due to the addition of coupling agents, the preparation process of polymers with star structures is more difficult to control than that of linear structures, and the quality fluctuates due to the fluctuations in coupling degree and coupling efficiency (generally the content of uncoupled two blocks is 5-20% by weight), but its melt viscosity is smaller than that of linear structures and is convenient for processing and use, but it still has limitations, such as inconvenience in construction and coating at ambient temperature. For this reason, the content of the two blocks is increased to achieve better initial adhesion and processability at ambient temperature. For example, the Chinese patent (CN105121583) increases the content of the two blocks to 50-90% by weight.

[0006] When the above polymers are used in hot melt adhesives, there is a shortcoming: it is difficult to well balance the relationship between the initial adhesion, lasting adhesion, peel strength and wettability with the adherend of the hot melt adhesive. Summary of the invention

[0007] In view of the problems existing in the prior art, the first object of the present invention is to provide a multi-component block copolymer composition, by controlling the vinyl aromatic hydrocarbon content, molecular weight and addition ratio in each block copolymer, so as to obtain a composition product with excellent comprehensive performance.

[0008] The second object of the present invention is to provide a method for preparing a multi-component block copolymer composition, which utilizes a three-step and two-step polymerization process to accurately and effectively control the physicochemical properties of each block copolymer, thereby quickly and accurately obtaining the corresponding block copolymer composition.

[0009] The third object of the present invention is to provide an application of a multi-component block copolymer composition, which is used together with a tackifying resin and a softener to prepare an adhesive composition for a polymer waterproof coiled material.

[0010] To achieve the above technical purpose, the present invention provides a multi-component block copolymer composition, wherein the block copolymer composition is obtained by copolymerizing raw materials including block copolymer A and block copolymer B; the mass ratio of block copolymer A to block copolymer B is 2-4:6-8;

[0011] The general structural formula of the block copolymer A is shown in Formula I:

[0012] Formula I: S1-D1-S2;

[0013] The general structural formula of the block copolymer B is shown in Formula II:

[0014] Formula II: S3-D2;

[0015] In formula I and formula II: S1, S2 and S3 are all vinyl aromatic homopolymer blocks, D1 and D2 are random copolymer blocks of two or more conjugated dienes; the weight average molecular weights of S1 and S2 are both less than the weight average molecular weight of S3; the mass percentage of the vinyl aromatic unit in the block copolymer A is 15-40%; the mass percentage of the vinyl aromatic unit in the block copolymer B is 10-30%; the content of the vinyl aromatic unit in the block copolymer A is greater than the content of the vinyl aromatic unit in the block copolymer B; the weight average molecular weights of the block copolymer A and the block copolymer B differ by ≤25%.

[0016] In the prior art, in the composition of triblock copolymer and diblock copolymer, the content of vinyl aromatics in the triblock copolymer and the diblock copolymer is the same, and the weight average molecular weight of the triblock is much greater than the weight average molecular weight of the diblock. In the present invention, a block copolymer composition is provided, in which the content of vinyl aromatics in the triblock copolymer and the diblock copolymer is different, but the weight average molecular weight of the triblock copolymer is the same or close to that of the diblock. The composition is used for hot melt adhesive for polymer waterproof coiled material, and the hot melt adhesive has high peel strength, good softener retention, excellent flexibility, and the coiled material is not easy to shift at high temperature, not easy to crack at low temperature, and has good waterproofness. With suitable tackifying resin and softener, the adhesive for polymer waterproof coiled material obtained has better aging resistance and resistance to softener exudation, and the service life is extended.

[0017] As a preferred embodiment, the vinyl aromatic content of block copolymer B is lower than that of block copolymer A by 2% to 7%.

[0018] When the vinyl aromatic content is low, the block copolymer composition has good initial adhesion and good wettability to the adhered surface, but the sustained adhesion and peel strength are relatively low, and the plasticizer retention is poor. When used in polymer waterproof membranes, the base layer and the polymer layer will separate and shift; when the vinyl aromatic content is high, the block copolymer composition has good sustained adhesion and peel strength, and the plasticizer retention is improved compared with the former, but the wettability to the base layer and the polymer layer is poor, and separation and shift will still occur; therefore, when the vinyl aromatic content in the block copolymer A is not higher than 25%, the content of copolymer B is appropriately reduced, and the mass ratio of the two is A:B=30:70~40:60; when the vinyl aromatic content of copolymer A is higher than 25%, the content of copolymer B in the composition is appropriately increased, and the mass ratio of the two is A:B=20:80~35:65; the mass ratio of A and B must be strictly implemented in accordance with the above requirements to obtain a product with excellent performance.

[0019] As a preferred solution, the weight average molecular weight of the block copolymer A and the block copolymer B is 50,000 to 200,000. More preferably, the weight average molecular weight of the block copolymer A and the block copolymer B is 80,000 to 180,000. The molecular weight of the block copolymer must be strictly in accordance with the above requirements. When the molecular weight is too small, the cohesion of the block copolymer composition is reduced, and when used as an adhesive, the retention of the softener therein is reduced; when the molecular weight is too large, the melt viscosity of the composition will increase significantly, affecting subsequent processing and use.

[0020] As a preferred solution, the weight average molecular weights of S1, S2 and S3 are all greater than 8000. Following the above requirements can ensure that the polymer has good separation properties and strong cohesion.

[0021] As a preferred solution, both D1 and D2 are composed of two different conjugated diene monomers. When the block copolymer composition is used to improve water resistance, halogen-free conjugated diene monomers are preferred, and 1,3-butadiene and isoprene are particularly preferred; when the block copolymer composition is used to improve adhesion, halogen-containing conjugated dienes are preferred; when the block copolymer composition is bonded to a non-polar material, 1,3-butadiene and isoprene are preferably used in combination; when the block copolymer composition is used to bond a polar material, a conjugated diene monomer with a polar group is preferred.

[0022] As a preferred solution, the mass ratio of the two different conjugated diene monomers is 2-8:8-2. If the vinyl aromatic content in the block copolymers A and B is too low, the cohesion will be too low, and the resulting waterproof roll will be delaminated and shifted; if the vinyl aromatic content is too high, the initial adhesion and flexibility of the resulting adhesive composition will be poor; by adjusting the ratio of the two conjugated dienes, block copolymer compositions with different solubility parameters can be obtained, and their high and low temperature properties can be adjusted at the same time, so that the block copolymer composition obtained has good compatibility with different materials, and the high and low temperature properties reach an ideal balance.

[0023] As a preferred solution, the vinyl aromatic hydrocarbon is at least one of alkyl-substituted styrene, alkoxy-substituted styrene and halogen-substituted styrene. When the block copolymer composition is to improve the waterproof performance, the vinyl aromatic hydrocarbon without halogen is preferred; when the contact surface of the block copolymer composition is a polar material, the vinyl aromatic hydrocarbon containing halogen or alkoxy is preferred from the perspective of wettability and adhesion with the polar material; styrene and alkyl-substituted styrene are preferred from the perspective of easy availability of raw materials and environmental protection. It is further preferred that the vinyl monomer in S1, S2 and S3 is styrene.

[0024] As a preferred solution, the ratio of the weight average molecular weight to the number average molecular weight of the block copolymer A is ≤1.1. More preferably, the ratio of the weight average molecular weight to the number average molecular weight of the block copolymer A is ≤1.06.

[0025] As a preferred solution, the ratio of the weight average molecular weight to the number average molecular weight of the block copolymer B is ≤1.1. More preferably, the ratio of the weight average molecular weight to the number average molecular weight of the block copolymer B is ≤1.06. When the ratio is small, the number of small molecules in the obtained block copolymer is smaller, and the block copolymer composition can obtain an adhesive composition with better high temperature performance.

[0026] As a preferred solution, the block copolymer composition further comprises a block copolymer C.

[0027] As a preferred solution, the mass percentage of the block copolymer C in the block copolymer composition is ≤10%.

[0028] As a preferred solution, when the block copolymer C is a linear structure, the weight average molecular weight is between 60,000 and 140,000.

[0029] As a preferred solution, when the block copolymer C is a star-shaped structure, the weight average molecular weight is between 120,000 and 260,000.

[0030] The weight average molecular weight of the block copolymer C must be strictly in accordance with the above requirements, because if the molecular weight is too high, the hot melt property will be poor, and if it is too low, the heat resistance stability will decrease. By making the molecular weight of such block copolymers within the above range, the block copolymer composition can form an adhesive composition with excellent hot melt property and heat resistance stability.

[0031] As a preferred solution, the mass percentage of the block polymer C in the block copolymer composition is ≤5%, and the ratio of its weight average molecular weight to number average molecular weight is 1.0 to 1.1.

[0032] As a preferred solution, the mass percentage of the vinyl aromatic unit in the block copolymer composition is 10 to 40%. When the content of all vinyl aromatic monomer units is too small, the cohesive force of the copolymer composition is low, and the holding force and peel strength of the adhesive composition obtained by using such block copolymer composition may deteriorate. When it is too large, the wettability of the obtained adhesive composition to the adherend surface deteriorates, and the adhesive force deteriorates.

[0033] As a preferred solution, the breaking strength of the block copolymer composition is 3-7 MPa, and the breaking elongation is 1100-1700%. When the breaking strength and breaking elongation of the block copolymer composition are within the above range, the block copolymer composition can obtain an adhesive composition with suitable initial adhesion, which is very beneficial for the close adhesion between the base layer and the polymer layer of the polymer waterproof coiled material, bringing good waterproof performance; if the breaking strength is too low, the peeling strength is low, and the waterproof coiled material will be delaminated and shifted; if it is too high, the initial adhesion decreases, and the waterproof sealing of the waterproof coiled material is poor. If the breaking elongation is too low, the flexibility may be poor, and it is easy to crack during processing and use; if it is too high, the shaping and dimensional stability are poor.

[0034] The present invention also provides a method for preparing a multi-component block copolymer composition, comprising:

[0035] 1) Under a nitrogen atmosphere, an alkane, a vinyl monomer and an initiator are uniformly mixed to carry out a polymerization reaction. When the vinyl monomer is completely polymerized, a conjugated diene monomer is slowly added. After the conjugated diene monomer is completely reacted, the vinyl monomer is added again to carry out a polymerization reaction. The reaction is terminated to obtain a block copolymer A;

[0036] 2) Under a nitrogen atmosphere, the alkane, the vinyl monomer and the initiator are uniformly mixed to carry out polymerization reaction. When the vinyl monomer is completely polymerized, the conjugated diene monomer is slowly added. After the reaction is completed, a block copolymer B is obtained;

[0037] 3) The raw materials including the block polymer A and the block polymer B are mixed uniformly, and then the solvent is removed and dried to obtain the product.

[0038] As a preferred solution, the polymerization temperature of the vinyl monomer is 40-60°C; the polymerization temperature of the conjugated diene is 60-80°C.

[0039] The present invention also provides an application of a multi-component block copolymer composition, wherein any of the above block copolymer compositions is used together with a tackifying resin and a softener to prepare an adhesive composition for a polymer waterproof coiled material.

[0040] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:

[0041] 1) The block copolymer composition provided by the present invention adjusts the different vinyl aromatic hydrocarbon contents of the triblock copolymer and the diblock copolymer, the special structures of the triblock copolymer and the diblock copolymer, and the same or similar number average molecular weight of the two, and further controls the ratio of the triblock copolymer to the diblock copolymer to form a copolymer composition with appropriate breaking strength and breaking elongation, thereby achieving a balanced optimization of the initial adhesion, holding adhesion, peel strength and wettability with the adherend in the copolymer composition.

[0042] 2) In the technical solution provided by the present invention, the hot melt adhesive for polymer waterproof roll prepared by using the above copolymer composition has excellent retention of the plasticizer in the hot melt adhesive due to the high vinyl aromatic content of the triblock, while providing higher holding force and peel strength; relying on the low vinyl aromatic content of the diblock, the obtained hot melt adhesive has excellent wettability and adhesion to common contact surface materials, and while maintaining higher holding force and peel strength, it can effectively prevent the separation and movement of the polymer layer and the base layer in the waterproof roll, and can also prevent the separation and movement of the roll and the contact surface that needs to be waterproof, such as cement surface, mud surface, asphalt surface, etc.

[0043] 3) In the technical solution provided by the present invention, the hot melt adhesive for polymer waterproof roll prepared by using the above copolymer composition, relying on the high proportion of the diblock copolymer with low vinyl aromatic content in the composition, makes the roll have better flexibility, air tightness and waterproof sealing. This polymer waterproof roll also has excellent crack resistance and puncture resistance. DETAILED DESCRIPTION

[0044] The present invention is illustrated by the following examples, which are not intended to limit the scope or implementation of the present invention.

[0045] The block copolymer composition and the adhesive composition of the present invention are described in detail below.

[0046] 1. Preparation of block copolymers

[0047] The copolymer A is first synthesized by a mature three-step sequential addition method, and then the copolymer B is synthesized by a two-step sequential addition method. In the second step of adding, the conjugated diene and the vinyl aromatic hydrocarbon are mixed and added. The two are mixed evenly in a colloid state according to the required proportion, and then the solvent is removed by a mature devolatilization method, and the desired product is obtained after drying.

[0048] In the present invention, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer block and block copolymer are obtained by converting the molecular weight using polystyrene as a calibrant using gel permeation chromatography. The testing instrument is a LC-20AD series gel permeation chromatograph from Shimadzu Corporation of Japan, and the detector is a RID-10A differential refractometer.

[0049] 2. Block copolymer compositions

[0050] The block copolymers A and B are synthesized by three-step sequential feeding and two-step sequential feeding methods, and the two are mixed in proportion in the glue liquid state. The block copolymer composition can contain only block copolymer A and block copolymer B, or it can contain block copolymers other than the aforementioned block copolymers A and B. Other block copolymer components can be added to the glue liquid and mixed evenly and then the solvent is removed, or the finished product after the mixed glue liquid of A and B is desolvated and mixed evenly with other block copolymers to obtain. Such a method obtains a block copolymer composition, and each parameter of each block copolymer therein can be flexibly adjusted, so that the performance of the block copolymer composition can be easily achieved as required. Excellent effect, while the balance performance of the obtained hot melt adhesive is optimized as required.

[0051] The breaking strength test of the obtained block copolymer composition is carried out according to ISO / R527-1996(E) standard, and the breaking elongation is carried out according to SH / T1610-2001 standard.

[0052] 3. Adhesive composition for polymer waterproofing membrane

[0053] The adhesive composition for polymer waterproofing coiled material of the present invention is characterized in that it contains at least the above block copolymer composition, a tackifying resin and a softener. As required, an elastomer, an antioxidant, an ultraviolet absorber, a filler, etc. other than the block copolymers A and B may be added.

[0054] According to the present invention, the block copolymer composition is used to make the adhesive composition for polymer waterproofing coiled material have excellent initial adhesion, peel strength, softener retention, flexibility and aging resistance.

[0055] Elastomer

[0056] In addition to block copolymers A and B, polystyrene-polybutadiene-polystyrene block copolymers, polystyrene-polyisoprene-polystyrene, polystyrene-polyethylene-polybutylene-polystyrene, polystyrene-polyethylene-polypropylene-polystyrene, polybutadiene, polyisoprene and natural rubber may also be added.

[0057] The amount of each elastomer added can be determined based on the properties of the elastomer and the desired adhesive composition requirements.

[0058] Tackifying resin

[0059] As the tackifying resin for the adhesive for the polymer waterproofing membrane, a known natural resin or synthetic resin can be used.

[0060] Natural resins such as rosin resin, terpene resin, etc.

[0061] Rosin resins such as rosin, wood rosin; hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.

[0062] Terpene resins such as α-pinene resin, β-pinene resin, aromatic modified terpene resin, hydrogenated terpene resin, terpene phenolic resin, etc.

[0063] Polymerized tackifying resins in synthetic resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, C5-C9 petroleum resins, hydrogenated petroleum resins, alicyclic petroleum resins, etc. Condensation tackifying resins include alkyl phenolic resins, rosin-modified phenolic resins, and xylene resins.

[0064] Among the above-mentioned tackifying resins, aliphatic petroleum resins, aromatic petroleum resins, and hydrogenated petroleum resins are preferred, and hydrogenated C5 resins are more preferred, because hydrogenated C5 resins have better aging resistance than unhydrogenated resins, and have a lower melting point than hydrogenated resins above C5, can melt quickly, and have better compatibility with block copolymers than other hydrogenated resins.

[0065] Softener

[0066] As a softener, liquid polymers such as aromatic process oil, paraffin process oil, naphthenic process oil, polybutene and polyisobutylene can be used. Among these softeners, naphthenic process oil, polybutene and polyisobutylene liquid rubber are preferred. Polybutene and polyisobutylene liquid rubber are more preferred. Because polybutene and polyisobutylene liquid rubber are more compatible with the polyconjugated diene segment of the block copolymer as a softener than naphthenic process oil, so liquid polyisobutylene and polybutene are not easy to seep out from the adhesive.

[0067] Antioxidants

[0068] Phosphates can be combined with environmentally friendly hindered phenol compounds such as β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and tris(2,2-di-tert-butylphenyl) phosphite, bis[(2,4-di-tert-butylphenyl) propionate] pentaerythritol diphosphite.

[0069] Adhesive component ratio

[0070] Relative to 30 parts by mass of the block copolymer composition of the present invention, the amount of tackifying resin added is 30 to 100 parts by mass, preferably 40 to 60 parts by mass. When the tackifying resin is too little, the initial instantaneous bonding force of the adhesive composition is insufficient, and during the preparation of the polymer waterproof roll, the polymer layer and the base layer will be displaced or the bonding between the two will not be tight enough, which will easily form a water channel and affect the waterproof performance of the roll; if the tackifying resin is too much, the cohesion and flexibility of the adhesive composition will be reduced, and the polymer waterproof roll will also be separated and displaced, or even cracked during construction and use.

[0071] The amount of the softener added is 10 to 30 parts by mass, preferably 12 to 25 parts by mass, relative to 30 parts by mass of the block copolymer composition of the present invention. When the amount of the softener is too little, the melt viscosity of the adhesive composition is too high, and it is inconvenient to process and use; when the amount of the softener is too much, the softener tends to ooze out.

[0072] In addition to block copolymers A and B, the elastomer may also include polystyrene-polybutadiene-polystyrene block copolymers, polystyrene-polyisoprene-polystyrene, polystyrene-polyethylene-polybutylene-polystyrene, polystyrene-polyethylene-polypropylene-polystyrene, polybutadiene, polyisoprene and natural rubber.

[0073] If polybutadiene and polyisoprene are used, the amount added needs to be reduced due to their low cohesive force, while polystyrene-polyethylene-polybutylene-polystyrene and polystyrene-polyethylene-polypropylene-polystyrene have poorer flexibility than block copolymers A and B, and should not be added in excess. In the adhesive composition, the amount of other elastomers added, except block copolymers A and B, relative to 30 parts by mass of the block copolymer composition of the present invention, should preferably not exceed 5 parts by mass.

[0074] The amount of antioxidant added can be determined according to the properties of each antioxidant and the properties and usage environment required for the resulting adhesive. Generally, the amount added is 0.1% to 0.5% by mass of the adhesive composition.

[0075] The method for producing the adhesive composition is not particularly limited, and a conventionally known method may be used, such as melting and kneading the components at a high temperature of 160° C. to 180° C. under nitrogen protection.

[0076] Example 1

[0077] A 5L stainless steel polymerization kettle with a jacket and a stirrer was fully replaced with N2, and 3000ml of cyclohexane, 0.1g of tetrahydrofuran and 27g of styrene were added. Warm water was passed into the jacket, and the materials in the polymerization kettle were heated to about 55°C while stirring. n-Butyl lithium cyclohexane solution was added to break the impurities in the polymerization kettle and the materials therein that could inactivate n-Butyl lithium, until the solution was light yellow, and then n-Butyl lithium cyclohexane solution (pure n-Butyl lithium was 2.31mmol) as an initiator was added to start the polymerization of styrene. After the styrene was completely polymerized, 196.8g of isoprene and 49.2g of butadiene were mixed uniformly in a measuring tank, and the temperature in the polymerization kettle was maintained above 60°C. The mixture was continuously added to the polymerization kettle, and the feeding time was maintained above 60min. After the feeding was completed, the reaction was continued for 5-20min. After the polymerization was completed, 27g of styrene was added. After the reaction of styrene was completed, 0.1g of ethanol was added to terminate the reaction, and block copolymer A was obtained. The obtained block copolymer A was added with 1g of primary antioxidant 1076 and 1g of secondary antioxidant 168. A portion of the colloid was taken, and the solvent was removed by steam condensation. The sample was dehydrated and dried using a hot roller to obtain a block copolymer A sample. Various tests were carried out and the remaining colloid was reserved for later use. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0078] A 5L stainless steel polymerization kettle with a jacket and a stirrer was fully replaced with N2, 3000ml of cyclohexane, 0.1g of tetrahydrofuran, and 45g of styrene were added, and the impurities were removed and the styrene polymerization was initiated in the same manner as in Example 1. 2.31mmol of initiator n-butyl lithium was added, and after the styrene reaction was completed, 204g of isoprene and 51g of butadiene were mixed, and the polymerization of isoprene and butadiene was completed according to the same operation and conditions as in Example 1, and 0.1g of ethanol was added to terminate the polymerization, thereby obtaining block copolymer B. The amount of antioxidant added, the desolvation and drying processes were the same as those of block copolymer A, the material ratios were shown in Table 1, and the physicochemical properties were shown in Table 2.

[0079] The amount of the copolymer A and B was calculated according to the dry glue A:B=40 / 60, the glue containing A and B was mixed evenly, the solvent was removed and dried to obtain 30 parts of a copolymer composition, of which A was 12 parts and B was 18 parts.

[0080] 30 parts of the copolymer composition were put into a mixer with a stirring blade, and 50 parts of tackifying resin (trade name Escorez 5400, produced by ExxonMobil Corporation of the United States), 15 parts of softener (polyisobutylene, polyisobutylene with a molecular weight of about 1000, such as PB-950 of Puyang Hengtai Petrochemical Co., Ltd.) and 1 part of antioxidant (Irganox1010) were added thereto. After the system was replaced with N2, mixing was carried out at 160-180°C for 30-60 minutes to prepare an adhesive composition for polymer waterproofing coiled materials. The adhesive performance test sample was obtained by coating a polyester film with a thickness of 25 μm, and the softener retention, initial adhesion and peel strength were evaluated for this sample. The results are shown in Table 3.

[0081] Comparative Example 1

[0082] The preparation process of this comparative example is exactly the same as that of Example 1, except that: the block copolymer A in Example 1 and the block copolymer X1 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, wherein A is 12 parts and D1 is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0083] The preparation process of block copolymer X1 is the same as that of block copolymer B in Example 1, and its vinyl aromatic content and weight average molecular weight are the same as those of block copolymer A. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0084] Comparative Example 2

[0085] The preparation process of this comparative example is exactly the same as that of Example 1, except that: the block copolymer A in Example 1 and the block copolymer X2 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, wherein A is 12 parts and D2 is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0086] The preparation process of block copolymer X2 is the same as the preparation process of block copolymer B in Example 1. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0087] Comparative Example 3

[0088] The preparation process of this comparative example is exactly the same as that of Example 1, except that: the block copolymer A in Example 1 and the block copolymer X3 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, wherein A is 12 parts and D3 is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0089] The preparation process of block copolymer X3 is the same as that of block copolymer B in Example 1, but there is only one conjugated diene. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0090] Comparative Example 4

[0091] The preparation process of this comparative example is exactly the same as that of Example 1, except that: the block copolymer A in Example 1 and the block copolymer X4 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, wherein A is 12 parts and D4 is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0092] The preparation process of block copolymer X4 is the same as the preparation process of block copolymer B in Example 1. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0093] Comparative Example 5

[0094] The preparation process of this comparative example is exactly the same as that of Example 1, except that the block copolymer X5 and the block copolymer B in Example 1 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, of which D5 is 12 parts and B is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0095] The preparation process of block copolymer X5 is the same as the preparation process of block copolymer A in Example 1. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0096] Comparative Example 6

[0097] The preparation process of this comparative example is exactly the same as that of Example 1, except that the block copolymer X6 and the block copolymer B in Example 1 are mixed evenly, the solvent is removed and dried to obtain 30 parts of a copolymer composition, of which D6 is 12 parts and B is 18 parts. The performance parameters of the adhesive composition prepared using the copolymer composition are shown in Table 3.

[0098] The preparation process of block copolymer X6 is the same as the preparation process of block copolymer A in Example 1. The material ratio is shown in Table 1, and the physicochemical properties are shown in Table 2.

[0099] Table 1 Material ratio of each block copolymer in Example 1 and Comparative Examples 1 to 6

[0100]

[0101] Table 2 shows the physicochemical properties of the block copolymers in Example 1 and Comparative Examples 1 to 6.

[0102]

[0103] Table 3 shows the performance parameters of the copolymer compositions in Example 1 and Comparative Examples 1 to 6

[0104]

[0105]

[0106] From the data in Table 1 and Table 2, it can be seen that copolymer X1 is a diblock copolymer with the same vinyl aromatic content and weight average molecular weight as copolymer A; copolymer X2 adjusts the amount of initiator, and the other material ratios are the same as copolymer B, to synthesize a diblock copolymer with the same vinyl aromatic content as copolymer A but a large difference in weight average molecular weight; copolymer X3 uses only one conjugated diene, and the other material ratios are the same as copolymer B, to synthesize a diblock copolymer with the same vinyl aromatic content as copolymer A and a similar weight average molecular weight; copolymer X5 and copolymer X6 use only one conjugated diene, and the other material ratios are the same as copolymer A to synthesize triblock copolymers.

[0107] From the data in Table 3, it can be seen that in Comparative Example 1, when a diblock copolymer with the same vinyl content as the triblock copolymer is used, the initial adhesion and peel strength of the obtained hot melt adhesive are reduced to varying degrees due to the reduced wettability of the adhered surface, and the retention rate of the softener is slightly reduced; in Comparative Example 2, when the weight average molecular weight of the diblock copolymer used is only about 1 / 2 of the weight average molecular weight of the triblock copolymer, the softener retention rate is greatly reduced, and the peel strength is significantly reduced. As in Comparative Examples 3 and 4, the conjugated diene unit in the diblock copolymer contains only one, and the performance of the obtained hot melt adhesive is still not as good as the block copolymer composition of the present invention. In Comparative Examples 5 and 6, a triblock copolymer containing only one conjugated diene is used, and the performance of the obtained hot melt adhesive is also not as good as the effect of the block copolymer composition of the present invention, which is similar to Comparative Examples 3 and 4.

Claims

1. A multi-component block copolymer composition, characterized in that: The block copolymer composition is obtained by copolymerizing raw materials including block copolymer A and block copolymer B; the mass ratio of block copolymer A to block copolymer B is 2-4:6-8; The general structural formula of the block copolymer A is shown in Formula I: Formula I: S1-D1-S2; The general structural formula of the block copolymer B is shown in Formula II: Formula II: S3-D2; In formula I and formula II: S1, S2 and S3 are all vinyl aromatic homopolymer blocks, D1 and D2 are random copolymer blocks of two or more conjugated dienes; the weight average molecular weights of S1 and S2 are both less than the weight average molecular weight of S3; the mass percentage of the vinyl aromatic unit in the block copolymer A is 15-40%; the mass percentage of the vinyl aromatic unit in the block copolymer B is 10-30%; the content of the vinyl aromatic unit in the block copolymer A is greater than the content of the vinyl aromatic unit in the block copolymer B; the weight average molecular weights of the block copolymer A and the block copolymer B differ by ≤25%.

2. A multi-component block copolymer composition according to claim 1, characterized in that: The weight average molecular weights of the block copolymer A and the block copolymer B are 50,000 to 200,000; the weight average molecular weights of S1, S2 and S3 are all greater than 8,000.

3. A multi-component block copolymer composition according to claim 1, characterized in that: Both D1 and D2 are composed of two different conjugated diene monomers; the mass ratio of the two different conjugated diene monomers is 2-8:8-2.

4. A multi-component block copolymer composition according to claim 1, characterized in that: The vinyl aromatic hydrocarbon is at least one of alkyl-substituted styrene, alkoxy-substituted styrene and halogen-substituted styrene.

5. A multi-component block copolymer composition according to claim 4, characterized in that: The ratio of the weight average molecular weight to the number average molecular weight of the block copolymer A is ≤1.1; The ratio of the weight average molecular weight to the number average molecular weight of the block copolymer B is ≤1.

1.

6. A multi-component block copolymer composition according to claim 1, characterized in that: The block copolymer composition further comprises a block copolymer C; the mass percentage of the block copolymer C in the block copolymer composition is ≤10%.

7. A multi-component block copolymer composition according to claim 6, characterized in that: When the block copolymer C is a linear structure, the weight average molecular weight is 60,000 to 140,000; when the block copolymer C is a star structure, the weight average molecular weight is 120,000 to 260,000.

8. A multi-component block copolymer composition according to claim 6, characterized in that: The mass percentage of the block polymer C in the block copolymer composition is ≤5%, and the ratio of its weight average molecular weight to number average molecular weight is 1.0-1.

1.

9. The multi-component block copolymer composition according to claim 1, characterized in that: The mass percentage of the vinyl aromatic unit in the block copolymer composition is 10-40%; the breaking strength of the block copolymer composition is 3-7 MPa, and the breaking elongation is 1100-1700%.

10. The method for preparing a multi-component block copolymer composition according to any one of claims 1 to 9, characterized in that: include: 1) Under a nitrogen atmosphere, an alkane, a vinyl aromatic monomer and an initiator are uniformly mixed to carry out a polymerization reaction. After the vinyl aromatic monomer is completely polymerized, a conjugated diene monomer is slowly added. After the conjugated diene monomer is completely reacted, the vinyl aromatic monomer is added again to carry out a polymerization reaction. The reaction is terminated to obtain a block copolymer A; 2) Under a nitrogen atmosphere, the alkane, the vinyl aromatic monomer and the initiator are uniformly mixed to carry out polymerization reaction. When the vinyl aromatic monomer is completely polymerized, the conjugated diene monomer is slowly added. After the reaction is completed, a block copolymer B is obtained; 3) The raw materials including the block polymer A and the block polymer B are mixed uniformly, and then the solvent is removed and dried to obtain the product.

11. A method for preparing a multi-component block copolymer composition according to claim 10, characterized in that: The polymerization temperature of the vinyl aromatic monomer is 40-60°C; the polymerization temperature of the conjugated diene monomer is 60-80°C.

12. Use of a multi-component block copolymer composition according to any one of claims 1 to 9, characterized in that: Application: Adhesive for waterproof membrane.

13. The use of a multi-component block copolymer composition according to claim 12, characterized in that: The adhesive comprises a block copolymer composition, a tackifying resin and a softener.

Citation Information

Patent Citations

  • Monovinylarene-conjugated diene block copolymer composition and preparation method and application thereof

    CN102453304A

  • Adhesive composition

    JP2016088971A

  • Adhesive composition comprising a block copolymer having a polyvinyl aromatic block and poly(vinyl aromatic / isoprene) block, articles, and methods of bonding

    US20210309893A1